Impact of Cryosublimation on Cord Blood Serum Composition - Skoryk, Anastasiia; Shevchenko, Mariia; Salnykov, Dmytro; Prokopiuk, Olga; Gorina, Olga (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):302